Cryoablation for fibroadenoma with liquid nitrogen based system: A retrospective analysis of prospectively collected data - Teodóra Filipov; Brigitta Teutsch; Dorina Vass; Boglárka Budinszki; Péter Hegyi; Attila Doros; Gábor Forrai; Pál Ákos Deák (PLoS ONE, 2026)
Background Fibroadenoma is the most common benign breast lesion found on core needle biopsies. Surgical excision is the standard of care for these lesions. This retrospective study aims to evaluate the safety and efficacy of liquid nitrogen-based cryoablation in treating multiple fibroadenomas, including large lesions. Methods A liquid nitrogen-based cryoablation system was used to treat histologically confirmed benign fibroadenomas under ultrasound guidance at Premier Med Healthcare, Training, and Research Institute between 2017 and 2022. The number and times of freeze-thaw-freeze treatment cycles and the number of cryoprobe relocations were determined according to the location and size of the fibroadenomas. Sequential cryoprobe relocation was performed in case of large or multiple fibroadenomas treated in one session. Patients underwent ultrasound examination follow-up visits for up to 12 months post-cryoablation. Data were analyzed descriptively. Changes in lesion size were evaluated using the Wilcoxon signed-rank test. A p-value < 0.05 was considered statistically significant. Results 78 women with a mean age of 34.2 ± 9.8 were included. The number of lesions per patient ranged from 1 to 4, with 60% having one lesion, 25% two, 13% three, and 3% four. Lesions were evenly distributed between the left (48.4%) and right (51.6%) breasts, with the upper outer quadrant being the most common location (28%). Lesion size, diameter of the largest dimension, ranged from 7 to 80 mm (mean 25 ± 10.9). The mean procedure time was 13 ± 10.4 minutes with 1−5 relocations per cryoprobe. In 76% of cases, a single freeze-thaw-freeze cycle was sufficient. Multiple cryoprobe relocations were used for larger or multiple lesions to ensure full coverage. The median volume reduction was 80.6% (IQR: 56.6–92.6) at 6 ± 1.5 months and 92.9% (IQR: 73.6−100) at 12 ± 1.5 months. The reduction observed at 12 months (mean follow-up of 16.3 ± 10 months) was statistically significant (p < 0.0001). One minor adverse event occurred (1/123 = 0.81% [95%CI: 0.02%−4.45%]) that resolved with conservative treatment. Conclusion Cryoablation with a liquid nitrogen-based system proved safe and effective, with 92.9% volume reduction at one year post-cryoablation for fibroadenoma. Sequential cryoprobe relocations preserve safety and efficacy, allowing the flexibility necessary for complete ablation of large or multifocal lesions. With the inclusion of a large patient cohort, our study further reinforces the clinical value of cryoablation and brings the technique one step closer to integration into routine practice.